2020
DOI: 10.1080/14992027.2020.1817994
|View full text |Cite
|
Sign up to set email alerts
|

Applied tele-audiology research in clinical practice during the past decade: a scoping review

Abstract: Objective: The purpose of this scoping review was twofold , (1) to provide information about the characteristics, type of service delivery, participant information and outcomes related to tele-audiology in clinical popluations, and (2) to describe documented facilitators and barriers to tele-audiology delivery from the perspectives of practitioners and service recipients. Knowledge of these findings can assist audiologists in considering remote service delivery options for their practices. Design: A scoping re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 50 publications
0
31
0
1
Order By: Relevance
“…This could explain the significant differences between NHS and private providers rating of the "Requirement for multiple technologies for each of the hearing aid manufacturers" as a barrier to telehealth delivery (Table 1). Muñoz et al (2020) reported rehabilitative audiology, including remote hearing aid fitting and adjustment, to be an area of significant potential for teleaudiology. Hearing aid fitting, adjustment, testing and counselling can be carried out through teleaudiology (Campos and Ferrari 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This could explain the significant differences between NHS and private providers rating of the "Requirement for multiple technologies for each of the hearing aid manufacturers" as a barrier to telehealth delivery (Table 1). Muñoz et al (2020) reported rehabilitative audiology, including remote hearing aid fitting and adjustment, to be an area of significant potential for teleaudiology. Hearing aid fitting, adjustment, testing and counselling can be carried out through teleaudiology (Campos and Ferrari 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although telehealth delivery of audiology services has been the subject of much discussion in recent years, clinical uptake has been slow, despite a growing body of evidence supporting the use of telehealth for audiology services (Munoz, Nagaraj, and Nichols 2021). Although many aspects of audiology have been validated for use in telehealth ) reports of it being used in routine clinical practice are still limited (Ratanjee-Vanmali, Swanepoel, and Laplante-Levesque 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, different audiological service deliveries via telepractice have been explored ( Swanepoel and Hall, 2010 ; Muñoz et al, 2021 ). Several applications for hearing screening have demonstrated the feasibility and reliability of telehealth ( Smits et al, 2013 ; Louw et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%